2008
DOI: 10.1086/524328
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-outbreak ofMycobacterium abscessusInfection Caused by Laboratory Contamination

Abstract: Although the source was never confirmed, our investigation suggests that this was a pseudo-outbreak of M. abscessus infection that resulted from contamination of mycobacterial cultures during incubation. Our findings emphasize the need for guidance on the disinfection of specimen incubators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…specimen contamination by NTM contained in tap water used to rinse mouth before sputum collection) [18]. Similarly, laboratories may be reporting an increased number of NTM because of contamination of reagents used in processing of specimens [19]. Therefore, isolation of NTM from clinical specimens should be evaluated carefully in the light of clinical information to assess their significance.…”
Section: Discussionmentioning
confidence: 99%
“…specimen contamination by NTM contained in tap water used to rinse mouth before sputum collection) [18]. Similarly, laboratories may be reporting an increased number of NTM because of contamination of reagents used in processing of specimens [19]. Therefore, isolation of NTM from clinical specimens should be evaluated carefully in the light of clinical information to assess their significance.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of a multisite pseudo-outbreak with an identified source. Other pseudo-outbreaks of bacterial infections have been described previously; however, they were limited to a single healthcare facility, and a local explanation was found [7][8][9].…”
mentioning
confidence: 70%
“…Ticks are known to transmit a large spectrum of emerging bacterial zoonotic pathogens [7] including Borrelia burgdorferi sensu lato (sl) [8], Anaplasma phagocytophilum [9], and Babesia spp. [ More recently it was shown that the prevalence of B. henselae and Borrelia burgdorferi sl DNA in the environmental I. ricinus populations sampled in different European sites was up to 40%.…”
mentioning
confidence: 99%
“…An increased number of NTM may be reported due to contamination of specimen during collection, contamination of reagents used in specimen processing, 25,26 or contamination of medical tools. 9 Therefore, patients testing positive for NTM should be closely assessed to ascertain the clinical significance of the laboratory result.…”
mentioning
confidence: 99%